2023
DOI: 10.3389/fneur.2022.1089981
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral biportal endoscopic lumbar interbody fusion enhanced the recovery of patients with the lumbar degenerative disease compared with the conventional posterior procedures: A systematic review and meta-analysis

Abstract: BackgroundMinimally invasive endoscopic technique is an important component of Enhanced Recovery After Surgery (ERAS) protocol for neurosurgery. In recent years, unilateral biportal endoscopic lumbar interbody fusion (ULIF) has been used in the treatment of lumbar degenerative diseases (LDD). This study aims to investigate whether ULIF could enhance the recovery of patients with LDD compared with the conventional minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) or posterior lumbar interbody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…With advancements in endoscopic instruments and surgical techniques, the incidence of complications in endoscopic TLIF has decreased dramatically in recent years. A recent meta-analysis showed that the incidence of complications in PE-TLIF was 10.1%, which is close to that of MIS-TLIF (12.7%); the incidence of complications in UBE-TLIF (7.8%) was also similar to that of MIS-TLIF (7.1%) [8,10]. The most common complications are dura tear, nerve injury, endplate injury, and screw misplacement.…”
Section: Complicationsmentioning
confidence: 82%
See 2 more Smart Citations
“…With advancements in endoscopic instruments and surgical techniques, the incidence of complications in endoscopic TLIF has decreased dramatically in recent years. A recent meta-analysis showed that the incidence of complications in PE-TLIF was 10.1%, which is close to that of MIS-TLIF (12.7%); the incidence of complications in UBE-TLIF (7.8%) was also similar to that of MIS-TLIF (7.1%) [8,10]. The most common complications are dura tear, nerve injury, endplate injury, and screw misplacement.…”
Section: Complicationsmentioning
confidence: 82%
“…A large amount of research has confirmed that PE-TLIF, UBE-TLIF, and MIS-TLIF all have the capacity to achieve satisfactory clinical effects, with no significant differences in mid-to long-term outcomes. Several meta-analyses have reported that both PE-TLIF and UBE-TLIF are superior to MIS-TLIF in early relief of low back pain, especially within three months after surgery; however, there is no significant difference between the alleviation of leg discomfort and the enhancement of the Oswestry Disability Index [7,8]. These results suggest that endoscopic TLIF could achieve adequate nerve decompression, with less ischemic damage to paraspinal muscles, ligaments, and posterior soft tissue.…”
Section: Clinical Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…First, bleeding can be prevented in advance by using radiofrequency ablation under the endoscopic field of vision, which can provide a clear surgical field of vision and reduce intraoperative bleeding [ 4 ]. Second, continuous fluid irrigation plays a vital role in controlling epidural and bone surface bleeding, which can reduce intraoperative blood loss [ 18 ]. Third, the adjacent pedicles will not be injured because a visible trephine is used for facetectomy [ 19 ], resulting in a small scope of bone resection and less bone bleeding, which is conducive to reducing intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the spinal endoscopic techniques and innovations in instrumentation have enabled spine surgeons to achieve decompression of the spinal canal and even interbody fusion through indirect visualization with the assistance of spinal endoscopy [ 1 ]. Unilateral biportal endoscopy (UBE) is an emerging minimally invasive spinal endoscopy technique that has attracted the attention of spine surgeons for its advantages of less blood loss, less trauma, and faster postoperative recovery [ 2 , 3 ]. Since Heo applied the UBE technique to transforaminal lumbar interbody fusion (TLIF) for the first time and got satisfactory outcomes in 2017 [ 4 ], the indications for UBE have gradually expanded to various degenerative spinal diseases.…”
Section: Introductionmentioning
confidence: 99%